Synthesis and consecutive reactions of a-azido ketones: a review - Faiz, Sadia; Zahoor, Ameer Fawad; Rasool, Nasir; Yousaf, Muhammad; Mansha, Asim; Muhammad Zia-Ul-Haq; Jaafar, Hawa Z. E. (MDPI, 2015)
This review paper covers the major synthetic approaches attempted towards the synthesis of α-azido ketones, as well as the synthetic applications/consecutive reactions of α-azido ketones.